(untitled) - Abbs, Brian (London, 1977)
The materials have been very carefully planned in order that the beginner can immediately see the relevance to him/herself of what is being learnt.
Keywords: English language,English language,Tiếng Anh,Tiếng Anh; Textbooks for foreign speakers,Spoken English,Giáo trình dành cho người nước ngoài,Tiếng Anh môn nói